A new approach towards SME’s consideration - Kostis C. Koutsopoulos (European Journal of Geography)
The definition of an SME may vary from country to country (for example, the definition in Germany has a limit of 255 employees, while in Belgium it can be 100), but in all of them they are regarded as the key drivers of the economy and represent its backbone. Indeed, SMEs provide innovations spread throughout regions to solve a series of challenges like unequal development, climate change, resource efficiency and social cohesion. In addition, they involve: job creation; unemployment reduction; significant contribution to growth in GDP; sustainable spatial growth; needed money flow; the seed to form large companies; and the development of appropriate technology. However, despite the importance of SMEs, there is considerable confusion over which characteristics should be used to express and evaluate them, in determining policies and programs to help and support them. The literature (Peters and Waterman, 1982; Amini, 2004; Radam et al.,2008) has attempted to answer these concerns, but the BALANCE project’s (Green and Stable -Bringing Sustainability and Environmental Action Together for Better Future) research has shown that nowadays such justifications cannot be accepted, because the failure to address these issues lies on the inability of the traditional approach (exclusive economic) in describing, and analyzing them.